Heterogeneous Photocatalytic Degradation of Anionic and Cationic Dyes Over Fe-Fullerene/TiO2 Under Visible Light - Meng, Za-Da; Zhu, Lei; Ye, Shu; Ghosh, Trisha; Ullah, Kefayat; Nikam, Vikram; Oh, Won-Chun (Asian Journal of Chemistry, 2013)
Photocatalytic decolorization of methylene blue, methylene orange and rhodamine B in the presence of iron-treated fullerene/titania photocatalyst in aqueous solution was studied under visible light. The prepared composite photocatalyst were characterized by XRD, TEM, SEM, EDX and photocalytic activity. Its photo catalytic degradation effect was observed in the cationic dyes (methylene blue and rhodamine B) and anionic dye (methyl orange) solution. The results showed that iron incorporation enhanced the decolorization rate of dyes. The photocatalytic degradation of a dye solution could be attributed to the combined effects by the photo-degradation of titania, the synergetic effects of adsorption and photo-Fenton of Fe component. The repeatability of photocatalytic activity was also tested.